Memodelkan Pertumbuhan Ekonomi Pada Pandemi Covid-19 Di Indonesia - Ni Kadek Puspa Adi Swari; Ni Luh Putu Suciptawati; Made Susilawati (Media Informasi Penelitian Kabupaten Semarang, 2023)
The Covid-19 pandemic has a huge impact on economic aspects, one of which is economic growth. BPS Indonesia noted that in February 2021 Indonesia's economic growth contracted by 2.19% which could lead to an economic recession so it must be overcome by recognizing the factors that influence it. The economic growth of a region can also be influenced by the economic growth of other regions. Modeling the economic growth of each province in Indonesia needs to incorporate spatial effects into it. The purpose of this study is to model the factors that are thought to affect Indonesia's economic growth in the covid-19 pandemic using spatial regression analysis. The factors used are government consumption, domestic investment, exports, and public consumption. The results showed that the SAR model produced a smaller AIC value with the largest value, namely an AIC value of 876.87 and an value of 97.16%.